Analysis of the Relationship Between Parental Support on Student GPA Achievement - Nahdiyaturrohmah, Nahdiyaturrohmah; Gunawan, Elysia Salsabila; Aprian, Muhamad Raifal; Tambunan, Kezya Marisca Eunice; Marina, Marsela Putri (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
This study explores the influence of study time, parental support, extracurricular activities, age, and participation in tutoring activities on students' Grade Point Average (GPA) achievement. Results show that parental support, in the form of motivation and learning facilities, has a significant influence on improving GPA, while extracurricular activities contribute to the development of learning skills and enthusiasm. Age did not show a direct relationship with GPA achievement, although 16-year-old students tended to have better results. In addition, participation in tutoring activities was shown to have a positive impact through additional study time and deepening of material. This study highlights the importance of synergy between time management, family support, and educational support programs in optimizing student learning outcomes.